Politiske skandaler i danske medier 1980-2010 - Blach-Ørsten, Mark (Politik, 2011)
This article presents an overview of the political scandal in Denmark from 1980 to 2010. The article focuses on two kinds of scandal: The political scandal that concerns a minister or a politician’s transgressions within the realm of politics, and the norm scandal that concerns a minister or a politician’s personal transgressions either in the role of minister/politician or as a private person. The article concludes that there has been a dramatic rise in the number of political scandals from 2000 and onwards, but also that this rise – with some exceptions – may be viewed as a sign of Denmark as a healthy liberal democracy.